Indigenous reporting of a national housing corporation - Brown, Alistair (Emerald Group Publishing Limited, 2018)
Purpose – The purpose of this paper is to assess the level of reporting compliance achieved by the National Housing Corporation (NHC) of Papua New Guinea in terms of local indigenous reporting expectations. Design/methodology/approach – Testing of a framework of indigenous accountability through indigenous enactments and regulations is conducted by textual analysis, which is informed by the theory of indigenous alternatives to assess the financial reporting compliance of the NHC of Papua New Guinea’s financial statements for years ending 2004-2013. Findings – Documentary evidence of the state auditor reports of the NHC’s financial statements reveals that the corporation’s financial reports are not submitted for audit on a timely basis and receive disclaimed audit opinions. Despite the clear indigenous reporting expectations raised by local legislative and regulatory instruments, the NHC is unable or unwilling to provide an accurate account of their activities. Practical implications – The lack of compliant reporting suggests that the planning, management and monitoring of the housing needs of residents of Papua New Guinea are compromised. There also appears merit in asking why parliament continues to fund the corporation given its difficulties in meeting local-level reporting expectations. Social implications – The results have wider implications for the reporting ideologies of indigenous-run housing corporations operating in other developing countries. It might be fruitful to meet local reporting expectations before taking on the specialized reporting that accompanies introduced western-oriented policies on housing. Originality/value – Accountability in relation to indigenous property management is constructed through a lens of reporting issues facing a developing country housing corporation.